STRENGTHENING CHARACTER EDUCATION IN REALIZE PROFILE PANCASILA STUDENTS THROUGH MAKING WALL MAGAZINE CHARACTER - Laila Tri Riana; Juliana R.Samawati; Farhan Rahman; Rahmatiya Mohamad; Abdul Rahmat (International Journal of Innovations in Engineering Research and Technology, 2022)
Profile Pancasila students are embodiment Indonesian students as student throughout life that has global competence and behaving in accordance with Pancasila values , with six characteristic main : faith , piety to Almighty God _ Esa , and morals Noble , Global Diversity , Collaborative , Independent , Reasonable critical , and creative . Destination project this that is as compass for educator nor student for develop character that has there is in self every individual . Profile student pancasila this could help build character across generations young and very influential for continuity nation , instill education character good applied to children at school basic , know and learn character with good as well as strengthen education character through profile student pancasila teach mutual cooperation and work same . education character have same essence and meaning _ with moral education and education morals . The goal is form personal participant educate , to become good and well behaved human being in accordance with creed .